The impact of cross border E-tailer's return policy on consumer's purchase intention. (March 2021) - Shao, Bingjia; Cheng, Zhendong; Wan, Lijuan; Yue, Jie
Abstract: Based on the signaling theory, cue utilization theory and halo effect theory, this paper establishes a theoretical model of the impact of return policy leniency on consumer purchase intention in the context of cross-border e-commerce (CBEC). The model is verified by the experimental data. Moreover, the mediating role of perceived quality and perceived risk and the moderating effects of port of shipment and product traceability code are significant. The results show that in the CBEC scenario, when the online retailers adopt a lenient return policy, the consumers have higher perceived quality and lower perceived risk, which in turn leads to a higher intention to purchase; When a consumer purchases the product which ships from domestic bonded warehouse or a product without a product traceability code present, the effect of the leniency of return policy on perceived quality and perceived risk is stronger.